2011
DOI: 10.1016/j.comppsych.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment of directly exposed survivors 7 years after the Oklahoma City bombing

Abstract: Objective-To prospectively examine the long-term course of psychiatric disorders, symptoms, and functioning among 113 directly exposed survivors of the Oklahoma City bombing systematically assessed at six months and again nearly seven years post-bombing. Methods-TheDiagnostic Interview Schedule/Disaster Supplement was used to assess predisaster and postdisaster psychiatric disorders and symptoms and other variables of relevance to disaster exposure and outcomes.Results-Total prevalence of PTSD was 41%. Seven y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 31 publications
4
34
1
Order By: Relevance
“…In comparison, for the non-bereaved participants, there were 10/113 (8.8%) who developed PTSD, which underscores bereavement as a risk factor for long-term PTSD (Arnberg et al, 2011). Further, our prevalence rates were lower than in studies of directly exposed victims from both natural and anthropogenic disasters (Bøe et al, 2011;Favaro, Zaetta, Colombo, & Santonastaso, 2004;Hull et al, 2002;North, Pfefferbaum, et al, 2011;North, Pollio, et al, 2011). This study concerned an event very remote to the homes of the survivors and that the beliefs common in people with PTSD about the world as dangerous (e.g., no place is safe) may have been easier to reevaluate by the survivors in their processing of the event, as compared to the more plausible (and realistic) negative beliefs about the world if the index trauma took place in or close to the survivors' homes.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…In comparison, for the non-bereaved participants, there were 10/113 (8.8%) who developed PTSD, which underscores bereavement as a risk factor for long-term PTSD (Arnberg et al, 2011). Further, our prevalence rates were lower than in studies of directly exposed victims from both natural and anthropogenic disasters (Bøe et al, 2011;Favaro, Zaetta, Colombo, & Santonastaso, 2004;Hull et al, 2002;North, Pfefferbaum, et al, 2011;North, Pollio, et al, 2011). This study concerned an event very remote to the homes of the survivors and that the beliefs common in people with PTSD about the world as dangerous (e.g., no place is safe) may have been easier to reevaluate by the survivors in their processing of the event, as compared to the more plausible (and realistic) negative beliefs about the world if the index trauma took place in or close to the survivors' homes.…”
Section: Discussionmentioning
confidence: 40%
“…Increased alcohol consumption after disasters has also been noted, although recent findings suggest that the onset of alcohol abuse may often precede the disaster exposure (North, Pfefferbaum, et al, 2011). Prevalence estimates of PTSD after natural disasters range from 4 to 60%, with the majority of studies reporting estimates below 30% (Neria et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have demonstrated the long-term effects of terrorist attacks on direct victims and their relatives (Baca et al, 2002;DiGrande et al, 2011;L. Ferrando et al, 2011;Kawana et al, 2001;North et al, 2011). It appears symptoms may be more stable 1 year after the traumatic event rather than in the immediate aftermath (Brewin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD in particular often follows a chronic course in the general population (Breslau et al, 1998;Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995) and after exposure to terrorist attacks (DiGrande, Neria, Brackbill, Pulliam, & Galea, 2011;Kawana, Ishimatu, & Kanda, 2001;North, Pfefferbaum, Kawasaki, Lee, & Spitznagel, 2011).…”
mentioning
confidence: 99%